Green space Access to the Disadvantaged using Park Service Area Analysis: A Study of Bhubaneswar (Indian Journal of Public Health Research & Development, 2026)
Urban green spaces (UGS) are widely recognized for their significant health and well-being benefits. However,recent research highlights increasing disparities in access to these spaces, particularly among disadvantagedgroups. This study investigates the accessibility of UGS for disadvantaged community groups in Bhubaneswar,Odisha, India.Methods: Disadvantaged communities, particularly slum settlements, were identified using high-resolutionsatellite imagery. Data on urban green spaces were sourced from previous studies. A network analysis wasconducted in QGIS to delineate Park Service Areas (PSAs) using a 500-meter walking distance threshold frompark entry points, assessing the accessibility of urban green spaces.Results: Among Bhubaneswar’s 67 wards, approximately 42 wards demonstrated that only 0–25% of slum areasfall within a 500-meter PSA. In 8 wards, 25–50% of slum areas were covered. Notably, only 9 wards showed75–100% coverage of slum areas by PSA. These findings reveal a significant deficit in UGS access for slum dwellersand residents of informal settlements.Conclusion: This study underscores the urgent need for spatially equitable planning of urban green spaces. Thefindings can inform urban planners and landscape designers in optimizing the distribution of green spaces andstrategically placing park entry points to enhance accessibility for marginalized communities.
Keywords: Urban green spaces, Disadvantaged community, Environmental justice, Bhubaneswar